Use of the Fluoride Varnish Billing Code in a Tertiary Care Center Setting. (March 2020) - Kim, Peter; Daly, Jeanette M.; Berkowitz, Sharon; Levy, Barcey T.
Introduction: Dental caries is the most common chronic disease in children from birth through 5 years of age. Application of fluoride varnish (FV) is recommended for children younger than 6 years every 3 to 6 months by the United States Preventive Services Task Force. The purposes of this study were to (1) assess use and reimbursement of Current Dental Terminology (CDT) D1206 and Current Procedural Terminology (CPT) 99188 codes, which are the billing codes for FV application; (2) determine when and by whom each FV code was used; and (3) summarize the associated clinical notes.Methods: Using the electronic medical record data warehouse from a single tertiary teaching hospital and its affiliated primary care clinics, the dates of service, departments, provider names, and patient identifiers associated with codes CDT D1206 and CPT 99188 were collected. The content of clinical notes was reviewed and summarized. The study period was from May 1, 2009 through May 17, 2019.Results: During the 10-year time period, CDT D1206 was used 5 times and CPT 99188 was used 35 times. FV was applied exclusively during well-child visits. Only pediatricians, and no family physicians, applied FV in this setting.Discussion: A single pediatrician championing for FV application increased both the completion of procedure and the appropriate billing in 2019.Conclusion: FV application has been likely underutilized in this Midwestern tertiary teaching hospital and its affiliated clinics. For both family medicine and pediatric offices, an advocate for caries prevention is likely needed for successful implementation of FV application at well-child visits.